Radiative forcing by light absorbing impurities in snow from MODIS surface reflectance data - Painter, Thomas H.; Bryant, Ann C.; Skiles, S. McKenzie (Geophysical research letters, 2012)
The episodic deposition of dust and carbonaceous particles to snow decreases snow surface albedo and enhances absorption of solar radiation, leading to accelerated snowmelt, negative glacier mass balance, and the snow‐albedo feedback. Until now, no remote sensing retrieval has captured the spatial and temporal variability of this forcing. Here we present the MODIS Dust Radiative Forcing in Snow (MODDRFS) model that retrieves surface radiative forcing by light absorbing impurities in snow cover from Moderate Resolution Imaging Spectroradiometer (MODIS) surface reflectance data. Validation of MODDRFS with a 7‐year record of in situ measurements indicates the radiative forcing retrieval has positive bias at lower values and slight negative bias above 200 W m−2, subject to mixed pixel uncertainties. With bias‐correction, MODDRFS has a root mean squared error of 32 W m−2 and mean absolute error of 25 W m−2. We demonstrate MODDRFS in the Upper Colorado River Basin and Hindu Kush‐Himalaya. Key Points MODDRFS determines surface radiative forcing by dust and carbonaceous particles MODDRFS is validated by a 7 year record of energy balance measurements Bias‐corrected MODDRFS has an RMSE of 32 W m‐2 and mean error of 0 W m‐2